Surface Finish Investigation on Anchor-Shaped lead castings - Thoguluva Raghavan, Vijayaram; Sivarao, Subramonian (THE INSTITUTION OF INDIAN FOUNDRYMEN, 2008)
An experimental investigation has been performed on the surface roughmess of anchor-shaped lead castings processed in green sand mould made from a readmade moulding sand mixture provided by a foundry sand manufacturing company. After the moulding process, liquid lead metal at a temperature of 320c were poured in the prepared cavities. In this study, test sample lead castings were taken for surface roughness analysis. With the aid of a digital profilometer, surface roughness analysis, Ra values were determined (R-Profile) at different locations randomly and only on the surface of castings for this study. The Ra data of lead castings were correlated with the quality of the green sand moulds made from the readymade moulding sand mixture.